1988
DOI: 10.1111/j.1471-0528.1988.tb06553.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy supplementation in the last trimester of pregnancy in East Java: I. Effect on birthweight

Abstract: Summary. The effect of two levels of energy supplementation in the last trimester of pregnancy on birthweight was tested in a controlled randomized trial in three villages in Madura, East Java. The high and low energy supplements provided 1·95 MJ (465 kcal) and 218 kj (52 kcal) per day respectively. In the baseline period the home diet provided on average 6·28 MJ (1500 kcal) (SD 2·1 MJ (499 kcal)) and41g(SD 13 g) of protein. The mean birthweight was 2835 g and the rate of low birth‐weight 12·2%. In the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 18 publications
2
48
0
Order By: Relevance
“…Lighter women gained relatively more weight during their pregnancy than heavier women, a result in keeping with other studies in East Java, Indonesia (19) , Pakistan (20) and Taipei, Republic of China (21) . The present study showed that supplementation had an insignificant effect on birth weight and LBW, in keeping with some studies (22)(23)(24)(25)(26)(27) , while other studies have reported a significant impact of supplementation on birth weight (12,(28)(29)(30)(31)(32) . The most recent food supplementation trial on undernourished women from the Gambia (12) reported considerably larger effects on birth weight.…”
Section: Discussionsupporting
confidence: 74%
“…Lighter women gained relatively more weight during their pregnancy than heavier women, a result in keeping with other studies in East Java, Indonesia (19) , Pakistan (20) and Taipei, Republic of China (21) . The present study showed that supplementation had an insignificant effect on birth weight and LBW, in keeping with some studies (22)(23)(24)(25)(26)(27) , while other studies have reported a significant impact of supplementation on birth weight (12,(28)(29)(30)(31)(32) . The most recent food supplementation trial on undernourished women from the Gambia (12) reported considerably larger effects on birth weight.…”
Section: Discussionsupporting
confidence: 74%
“…40 kg 6,21,22 , and a PPW cut-off of 40 kg is the most commonly cited figure in developing countries used to assess risk of various pregnancy outcomes. Ideally, PPW should be taken before the woman is diagnosed as pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…105,114 Moreover, other studies showed no impact on maternal weight gain. 116,117 In the few studies that examined effects on the stillbirth 104,105 and perinatal mortality 104,105,118 rates, reductions were seen. The largest of these studies 104 was undertaken in The Gambia, where, in an RCT, chronically undernourished pregnant women were provided a higher-energy supplement (3780 kJ), largely toward the last trimester, with little micronutrient content.…”
Section: Tontisirin Et Al 110mentioning
confidence: 99%
“…Kardjati et al 116 East Java, Indonesia; rural setting; double-blind, randomized, controlled trial (DBRCT)…”
Section: Balanced Protein-energy Supplementationmentioning
confidence: 99%